Black liberation : a comparative history of Black ideologies in the United States and South Africa - Fredrickson, George M., 1934-2008 (New York : Oxford University Press, 1995)
"In Black Liberation, George Fredrickson offers a fascinating account of how blacks in the United States and South Africa came to grips with the challenge of white supremacy. He reveals a rich history - not merely of parallel developments, but of an intricate, transatlantic web of influences and cross-fertilization. He begins with early moments of hope in both countries - Reconstruction in the United States, and the liberal colonialism of British Cape Colony - when the promise of suffrage led educated black elites to fight for color-blind equality. A rising tide of racism and discrimination at the turn of the century, however, blunted their hopes and encouraged nationalist movements in both countries. Fredrickson teases out the connections between movements and nations, examining the transatlantic appeal of black religious nationalism (known as Ethiopianism), and the pan-Africanism of Du Bois and Garvey. He brings to vivid life the decades of struggle, organizing, and debate, as blacks in the United States looked to Africa for identity and South Africans looked to America for new ideas and hope. The book traces the rise of Communist influence in black movements in the two nations in the 1920s and '30s, and the adoption of Gandhian nonviolent protest after World War II. The story of India's struggle, however, was not to be repeated in either America or South Africa: in one nation, nonviolence revealed its limitations, encouraging splits in the civil rights movement; in the other, it failed, fostering an armed struggle against white supremacy. Fredrickson brings the story up through the present, exploring the divergence between African-American identity politics and the nonracialism that has triumphed in South Africa."--Jacket
Palladium of the people's liberties: the suffrage question and the origins of Black protest -- Ethiopia shall stretch forth her hands: Black Christianity and the politics of liberation -- Protest of the talented tenth: Black elites and the rise of segregation -- Africa for Africans: Pan-Africanism and Black Populism -- Self-determination for Negroes: Communists and Black freedom struggles, 1928-1948 -- We shall not be moved: nonviolent resistance to white supremacy, 1940-1965 -- Black man you are on your own: Black Power and Black consciousness. rc.
Includes bibliographical references (pages 325-366) and index.
Keywords: Civil rights movements -- South Africa -- History; African Americans -- Politics and government; Black people -- South Africa -- Politics and government; Pan-Africanism -- History; Black nationalism -- United States -- History; Afro-Americans -- politics & government; Black nationalism -- United States -- History; History